Three Frontiers for the Future of Biodiversity Research Using Citizen Science Data. (11th November 2020) - Callaghan, Corey T; Poore, Alistair G B; Mesaglio, Thomas; Moles, Angela T; Nakagawa, Shinichi; Roberts, Christopher; Rowley, Jodi J L; VergÉs, Adriana; Wilshire, John H; Cornwell, William K
Abstract: Citizen science is fundamentally shifting the future of biodiversity research. But although citizen science observations are contributing an increasingly large proportion of biodiversity data, they only feature in a relatively small percentage of research papers on biodiversity. We provide our perspective on three frontiers of citizen science research, areas that we feel to date have had minimal scientific exploration but that we believe deserve greater attention as they present substantial opportunities for the future of biodiversity research: sampling the undersampled, capitalizing on citizen science's unique ability to sample poorly sampled taxa and regions of the world, reducing taxonomic and spatial biases in global biodiversity data sets; estimating abundance and density in space and time, develop techniques to derive taxon-specific densities from presence or absence and presence-only data; and capitalizing on secondary data collection, moving beyond data on the occurrence of single species and gain further understanding of ecological interactions among species or habitats. The contribution of citizen science to understanding the important biodiversity questions of our time should be more fully realized.